Food quality and business aspects within MSMEs in Vietnam - Hernandez, Ricardo; Nguyen, Manh Cuong (2024)
The document explores the relationship between food quality and business practices among MSMEs in Vietnam, focusing on data from rural, peri-urban, and urban districts collected under the SHiFT initiative. Sampling 1,627 food businesses, the study evaluates food quality using the adjusted GDQS for diversity and healthiness and the NOVA classification for processing levels.